1992
DOI: 10.1128/iai.60.4.1295-1301.1992
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 response of epithelial cell lines to bacterial stimulation in vitro

Abstract: This study demonstrated that epithelial cell lines secrete interleukin-6 (IL-6) in response to stimulation with gram-negative bacteria. Human epithelial cell lines of urinary tract origin (A-498 and J82) and of intestinal origin (HT-29 and Caco-2) were analyzed for the secretion of IL-6 by using the B9 bioassay. The supernatants from cells maintained with culture medium were used to assess the constitutive production of IL-6. The supernatants from cells exposed to Escherichia coli strains, lipopolysaccharide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
73
1
2

Year Published

1993
1993
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(86 citation statements)
references
References 24 publications
10
73
1
2
Order By: Relevance
“…The fimbriae stimulate mucosal inflammation and the production of inflammatory mediators by epithelial cells. Although fimbriae themselves can trigger cell activation (Hedges et al, 1992;Svensson et al, 1994;Hedlund et al, 1996), they also dock the bacteria to sites at which receptors are expressed and may influence the host response by presenting other bacterial components, such as LPS, to these receptors. This study demonstrated that type 1 fimbriae deliver LPS to CD14-negative host cells and that the responses are partly TLR4 dependent.…”
Section: Discussionmentioning
confidence: 99%
“…The fimbriae stimulate mucosal inflammation and the production of inflammatory mediators by epithelial cells. Although fimbriae themselves can trigger cell activation (Hedges et al, 1992;Svensson et al, 1994;Hedlund et al, 1996), they also dock the bacteria to sites at which receptors are expressed and may influence the host response by presenting other bacterial components, such as LPS, to these receptors. This study demonstrated that type 1 fimbriae deliver LPS to CD14-negative host cells and that the responses are partly TLR4 dependent.…”
Section: Discussionmentioning
confidence: 99%
“…A number of intriguing hypotheses involving the role of P fimbriae in UTI have been suggested. Svanborg and colleagues (Hedges ef a/., 1991;1992;Under ef a/., 1988;1990) propose that induction of inflammation including recruitment of potymorphonuclear leucocytes and triggering of secretion of interleukin-6 is caused by the delivery of lipopolysaccharide (LPS) by bacteria adhering by P To our knowledge, true isogenic mutants of pap have not previously been constructed in virulent clinical isolates of E. coii. However, the contribution to virulence of P fimbriae has been tested using various mutants and transformants.…”
Section: Discussionmentioning
confidence: 99%
“…Many cell types produce this potent protein [41][42][43][44][45][46], and elevated levels of IL-6 are found in several different conditions [47][48][49][50][51][52][53]. Bacterial products [54,55] and various viruses [56,57] stimulate IL-6 production. High levels could be due to differences in responses to various stimuli, genetic polymorphisms, or a deficient interplay in the cytokine network, for instance with reduced production of IL-10 [58,59].…”
Section: Factors That Increases Il-6 Levelsmentioning
confidence: 99%